Sanksi Pembunuhan dengan Sengaja Perspektif Hukum Pidana Islam dan Hukum Positif - Andrianto, Fredy (Al-Mazaahib: Jurnal Perbandingan Hukum, 2022)
This article seeks to uncover criminal sanctions for intentional murder from the perspective of Criminal Law and Islamic Criminal Law. One form of murder that is very detrimental is intentional murder. This type of research is library research, using a normative-juridical approach and the nature of this article is descriptive-analytical-comparative. The research results show that the intentionality element can be seen in the tools used. If the murderer uses a tool or weapon to kill, it includes intentional murder. The purpose of punishment in Islamic law is not only to prevent criminal acts but following the objectives of maqasid as-syari'ah, namely hifz an-nafsi (body-body protection). In Islamic criminal law, the punishment for intentional murder is   qişāş, diyat, or ta’zīr, depending on the judge's decision. Meanwhile, the purpose of punishment in criminal law in Indonesia is based on three basic principles of punishment, namely retributive, relative, and combined. In positive law, the punishment for intentional murder, according to Article 340, is the death penalty. This means that there are few similarities between the two Islamic and Positive criminal laws, which open up the possibility of the death penalty being imposed on murderers.